2015
DOI: 10.4172/2157-7439.1000274
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Gold Nanorod Conjugates for Preclinical Biomedical Research

Abstract: Gold nanorods with a peak absorption wavelength of 760 nm were prepared using a seed-mediated method. A novel protocol has been developed to replace hexadecyltrimethylammonium bromide on the surface of the nanorods with 16-mercaptohexadecanoic acid and metoxy-poly(ethylene glycol)-thiol, and the monoclonal antibody HER2. The physical chemistry properties of the conjugates were monitored through optical and zeta-potential measurements to confirm surface chemistry changes. The efficiency of the modifications was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…One such study found that the use of prolate (1D stretch) ellipsoidal nanoparticles exhibited greater macrophage evasion in vivo and greater biodistribution in vivo suggesting a longer therapeutic window and escape potential from the reticularendothelial system (RES) compared to spherical analogs [17]. Moreover, on a morphology built to escape the reticular-endothelial system (RES) and to possess higher capability of surface modification, gold nanorods conjugated with HER2 antibodies on their surface were shown to associate with HER2 positive cell lines and tumors in murine models with high efficacy compared to the more traditional spheroid nanoparticles when considering their negative effects in general histological studies of inflammation in the liver [18,19]. For cellular uptake, Ridolfo's group found that dexamethasone loaded worm-like biodegradable nanoparticles possessed a significant capability of internalization in retinal cells despite their constituent materials across the board [20].…”
Section: Introductionmentioning
confidence: 99%
“…One such study found that the use of prolate (1D stretch) ellipsoidal nanoparticles exhibited greater macrophage evasion in vivo and greater biodistribution in vivo suggesting a longer therapeutic window and escape potential from the reticularendothelial system (RES) compared to spherical analogs [17]. Moreover, on a morphology built to escape the reticular-endothelial system (RES) and to possess higher capability of surface modification, gold nanorods conjugated with HER2 antibodies on their surface were shown to associate with HER2 positive cell lines and tumors in murine models with high efficacy compared to the more traditional spheroid nanoparticles when considering their negative effects in general histological studies of inflammation in the liver [18,19]. For cellular uptake, Ridolfo's group found that dexamethasone loaded worm-like biodegradable nanoparticles possessed a significant capability of internalization in retinal cells despite their constituent materials across the board [20].…”
Section: Introductionmentioning
confidence: 99%